Upaya Preventif Solusi Tindak Pidana Korupsi Berbasis Teknologi Aproach Blockchain Open Ladger System : (Studi Kasus Anggota DPRD Kota Surabaya) (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Corruption problems have occurred involving members of the Surabaya City DPRD, the defendant Syaiful Aidy, S.H. Setiawan offered a profit sharing of 10%-15% to the defendant Syaiful Aidy, S.H. The results of the corruption trial committed by the defendant Syaiful Aidy, S.H have been decided with the verdict number 131/Pid.Sus/TPK/2019/PN.SBY. Public concerns and declining trust in government financial management are caused by the many individuals involved in corrupt practices. The existence of the Blockchain Open Ledger System provides a solution for financial management that aims to reduce the number of corruption in Indonesia. In this research, the method used is a literature review that refers to previous studies listed in journals and articles. The results of this study show that the defendant has violated 4 elements (1) Every individual (2) which aims to benefit themselves, others, or a corporate entity (3) by abusing the authority, opportunity, or resources they have due to their position or position (4) can harm the state's finances or economy. A blockchain system can serve as a preventive measure in the management of the state's financial budget by providing clear transparency regarding the flow of funds. This allows the public to monitor the movement of the budget directly, so that in the event of irregularities or discrepancies, the perpetrators and problems can be identified.